Trauma-Induced Heterotopic Ossification Regulates the Blood-Nerve Barrier - Gugala, Zbigniew; Olmsted-Davis, Elizabeth A.; Xiong, Yuqing; Davis, Eleanor L.; Davis, Alan R. (Frontiers in Neurology, 2018)
De novo bone formation can occur in soft tissues as a result of traumatic injury. This process, known as heterotopic ossification (HO), has recently been linked to the peripheral nervous system. Studies suggest that HO may resemble neural crest-derived bone formation and is activated through the release of key bone matrix proteins leading to opening of the blood-nerve barrier (BNB). One of the first steps in this process is the activation of a neuro-inflammatory cascade, which results in migration of chondro-osseous progenitors and other cells from both the endoneurial and perineurial regions of the peripheral nerves. The perineurial cells undergo brown adipogenesis, to form essential support cells, which regulate expression and activation of matrix metallopeptidase 9 (MMP9) an essential regulatory protein involved in opening the BNB. However, recent studies suggest that, in mice, a key bone matrix protein, bone morphogenetic protein 2 (BMP2) is able to immediately cross the BNB to activate signaling in specific cells within the endoneurial compartment. BMP signaling correlates with bone formation and appears critical for the induction of HO. Surprisingly, several other bone matrix proteins have also been reported to regulate the BNB, leading us to question whether these matrix proteins are important in regulating the BNB. However, this temporary regulation of the BNB does not appear to result in degeneration of the peripheral nerve, but rather may represent one of the first steps in innervation of the newly forming bone.